A novel photoelectrochemical sensor developed by PLA/CB biopolymer associated with SiO2/WO3 for the imidacloprid determination - Oliveira Fernandes, Julia; dos Santos Fernandes, Juliana; Sabbatini Capella Lopes, Claudio; Ferreira Braz, Bernardo; Pessôa Oliveira, Guilherme; Machado Dornellas, Rafael; Silva Semaan, Felipe; Soares Archanjo, Braulio; Schwingel Ribeiro, Emerson [UNESP]; Erthal Santelli, Ricardo; Henrique Cincotto, Fernando (Wiley, 2024)
The 3D photoelectrochemical cell was developed with epoxy resin and a working composite electrode produced with a blend of 3D printer commercial conductive filament of polylactic acid biopolymer and carbon black (PLA/CB) mixed with silica/tungsten (VI) oxide (SiO2/WO3) synthesized was used for the determination of imidacloprid in water samples. Imidacloprid is a neonicotinoid pesticide considered potentially neurotoxic, and investigating its presence in aquatic environments is of great importance. The PLA/CB/SiO2/WO3 sensor was morphologically characterized by scanning electron microscopy. Photoelectrochemical performance of the composite sensor was evaluated by chronoamperometry, electrochemical impedance spectroscopy and cyclic voltammetry. In the presence of light (on) using differential pulse voltammetry in borate buffer solution (0.1 mol L−1, pH 7.0), the modified sensor exhibited a linear range of 0.15–93.70 μmol L−1 and with a limit of detection of 0.04 μmol L−1 to determine imidacloprid. The modified sensor did not present interferences for K+ and Fe3+ ions, carbendazim, glyphosate and thiamethoxam pesticides. Furthermore, the recovery in spiked samples successfully determined the presence of imidacloprid pesticide in tap water and natural river surface water.
Keywords: 3D printer; carbon black; imidacloprid pesticide; mixed oxide; photoelectrochemical sensor; polylactic acid